STRATEGI PELESTARIAN SINTREN Studi Kasus di Brebes - Devi, Wika Soviana (Fakultas Ilmu Budaya Universitas Diponegoro, 2012)
The traditional performing art of sintren is distinctive art flourished in northern coast of Java such as Brebes area. This kind of sintren performing art requires some conditions and rites that must be fulfilled for stage performance. The art of sintren has a background folklore who was later appointed into a show which is magical. To understand the art of sintren a collection and an analysis of data were obtained through interview, observation, and study of documents pertaining the art show of sintren. Performances of sintren exercised by some personnels, one is a kawih or sinden as a singer for sintren, to call down the nymphs of sintren, a sintren dancer and musicians. Sintren dancer who was possessed by sintren nymph will change clothes to be beautiful by hand and body bound and put in confinement. Brebes communities have recognized sintren performances as magical performances served at night and on certain occasions.